(untitled) (Our Nature, 2017)
The impact of artisanal refining of crude oil on the river bed sediments of the study area was investigated by assessing some quality properties. The result showed some consistency across the stations of the study area; however there were some differences between the values of the test stations and control station indicating some level of impacts on the quality of the sediments. The mean values of the test stations are pH 3.3±0.7, E. conductivity -10.2±3.7 mS/cm, Salinity 19.0±4.0‰, PO43- 401.8±67.0 mg/kg, SO42- 279.8±52.8 mg/kg, NO3- 58.0±22.9 mg/kg, SO2 215±100.2 mg/kg, Cl- 97.4±89.8 mg/kg, TOM 45.6±51.4%, K+ 1.054±0.3 meq/100g, Na+ 6.385±2.5 meq/100g and Ca2+ 0.756±0.6 meq/100g while that of the control values are 4.15±0.55, 11.0±0.0, 12.2±0.6, 428.25±12.75, 294.9±8.2, 76.8±15.2, 148.75±23.75, 126±99, 20. 9±4.1, 0.798±0.34, 5.639±1.383 and 0.261±0.128, respectively. The result indicated that the said activities affected the pH, PO43-, SO42-, NO3-, Cl- etc. of the study area; as these values were consistently lower than that of the control station. Again some of the quality properties were higher or lower than those of the control station and some related studies within and outside the region of the study area indicating some impacts which could be mostly anthropogenic. These impacts if not checked and the make–shift refining of the crude oil stopped by the appropriate regulatory bodies could have some adverse effects on the aquatic life quality of the ecosystem.